WILL BRAIN GROWTH BE AN ADAPTATION TO THE ENVIRONMENTAL TOLERANCE CRITERION IN THE LARVAE CONTROLLING SPECIES GAMBUSIA PUNCTATA POEY, 1854? - Argota-Pérez, George (2021)
The aim of the study was to measure brain growth in the larval control species Gambusia punctata Poey, 1854. The study was carried out in March 2021 and corresponded to two exposure stations in the lower part of the Almendares River (Havana, Cuba). For the sampling, a professional rectangular 60 x 50 x 45cm jamo was used and mesh size of 0.5cm. Eighteen male individuals (station A = 11, station B = 7) well identified by their gonopod were sampled. For the extraction of the brain, the individuals were placed in a ventral position where the containment was by means of a smooth clamp. With another bidentate dissection forceps, the cephalic region was peeled off until the brain was visualized, where its extraction was carried out with new smooth forceps until conization was left in the anatomical-cerebral region. Statistically significant differences were found in the brain growth of individuals between sampling stations A and B. It is concluded that, it is necessary to deepen in various analyzes to demonstrate, the hypothesis that the greater growth of the brain in males of the larval bioregulatory species G. punctata obeys the criterion of environmental tolerance, since from the base of empirical methods by observation and measurements that were carried out, it only meant a preliminary knowledge.